Assessing nursing students’ sex knowledge and sexual attitudes: implications for primary health care - Hoi, Nga Ng; Kam, Weng Boey (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Health professionals, especially nurses, in primary care setting are considered most appropriate for providing sexual health care. To provide quality sexual health care, nurses should have adequate sex knowledge and hold positive attitude towards sexuality. However, nurses’ perceived inadequate knowledge and negative attitudes towards sexuality were reported to be two major barriers to sexual health care, yet little is known about these barriers among nursing students in Hong Kong. This study was conducted to examine sex knowledge and attitudes towards sexuality among nursing students in Hong Kong. Methods A cross-sectional study was conducted on the first year nursing students (N= 258) who were recruited to participate via convenience sampling. The General Sexual Knowledge Scale (GSKS) and Attitude towards Sexuality Scale (ATSS) were used to collect data for this study. The data were analysed by descriptive statistics and independent t-test. Results Sex knowledge was 10.4 ± 3.5 and sexual attitude was 32.9 ± 4.6 indicating nursing students’ sex knowledge was poor and their sexual attitudes were neutral. Sex knowledge was positively related to the sexual attitudes (r = 0.47, p < .01). The attitudes were more liberal in students aged 20 years old or above than students aged 19 or below. Sexual attitudes were also more liberal among students who did not reported religious affiliation than students who did. Conclusions Knowledge and positive attitudes regarding human sexuality needed to be promoted among nursing students. Findings from this study provided useful information in preparing nursing students to render high quality sexual health care in primary care settings.